LGBTQ as the Rights in Turkey: Past, Present and Future Conditions - Nikolet, Talabos Dávidné Lukács (Pancasila and Law Review, 2024)
Sexuality is defined as one's thoughts, feelings, desires, and actions toward other people. The way a person communicates their sexual wants is what makes them human. It is possible to classify sexuality as a human right that each individual possesses, and that is immune to external interference. The lives of LGBTQ individuals continue to be focal points in the realms of social, political, and cultural discourse in many countries. Lesbian, gay, bisexual, and transgender are gender identities or sexual orientations that an individual is legally entitled to own. The recognition and protection of human rights for the LGBTQ have become a critical issue in global human rights discussions. This journal paper offers a thorough examination of Turkey's LGBTQ rights situation. The article examines the advancements made in LGBTQ rights across time through social movements, attitudes, and activism. However, it also draws attention to enduring obstacles that prevent LGBTQ people from achieving complete equality, such as prejudice, assault, and murky legal issues. To support ongoing efforts to promote inclusivity and equality for all people, regardless of sexual orientation or gender identity, this article attempts to provide insights into the intricate interaction of legal, social, and cultural aspects defining LGBTQ rights in Turkey. Therefore, through this article, the author will explain the past, present, and future of LGBTQ people in Turkey.